Precursors to effectiveness of public procurement audits for Constituency Development Funds (CDF) in Kenya - Achuora, John; Arasa, Robert; Ochriri, George (European Scientific Journal, 2012)
This study examined the factors that affect effectiveness of public procurement audits for constituency development funds in Kenya. Specifically it sought to investigate the effect of the legal framework, auditor’s specific professional qualities, technical audit factors and client-related factors on effectiveness of public procurement audits. A descriptive research design was employed, using a stratified random sampling to ensure representativeness. Both quantitative and qualitative methods of data analysis were used. Descriptive statistics as well as regression analysis were used to facilitate examination of the relationship between the variables of interest. The study findings indicate that technical audit factors have greatest influence on effectiveness of public procurement audit, followed by regulatory framework, client related factors and auditor’s professional qualities respectively. The study recommends that a summarized regulatory framework for CDF procurement management be prepared by policy makers, more public auditors be trained on public procurement audit and the CDF managers be exposed to audit as a positive management tool.
Keywords: Legal framework; Auditor’s specific professional qualities; Technical audit factors and client-related factors; Public procurement audits; Constituency development funds; Effectiveness